Circular economy business models: The state of research and avenues ahead - Ferasso, Marcos; Beliaeva, Tatiana; Kraus, Sascha; Clauss, Thomas; Ribeiro‐Soriano, Domingo (Business strategy and the environment, 2020)
This study investigates how the circular economy and business models are related in the current business and management literature. Based on bibliometric analytical procedures, 253 articles were retrieved from the Scopus, Web of Science, and ScienceDirect scientific databases. The articles were analyzed according to network analysis principles, and key terms were mapped into a network. We used VOSviewer to build the network, explore the most‐researched terms and their relationships, and identify less‐explored terms and research gaps. We furthermore conducted a qualitative review of selected publications to provide an illustration of quantitative results and delve deeper into the research topics. The main findings revealed the networks of current topics as they appear in the publications such as business models, the circular economy, circular business models, value, supply chain, transition, resource, waste, and reuse, and their most prevalent relationships. The results also highlighted several emerging topics such as those connected with managerial, supply‐side, demand‐side, networking, performance, and contextual considerations of circular business models.